Hydroxyl radical generation in electro-Fenton process with a gas-diffusion electrode: Linkages with electro-chemical generation of hydrogen peroxide and iron redox cycle - Yatagai, Tomonori; Ohkawa, Yoshiko; Kubo, Daichi; Kawase, Yoshinori (Journal of environmental science and health. Part A, Toxic/hazardous substances & environmental engineering, 2017)
The hydroxyl radical generation in an electro-Fenton process with a gas-diffusion electrode which is strongly linked with electro-chemical generation of hydrogen peroxide and iron redox cycle was studied. The OH radical generation subsequent to electro-chemical generations of H 2 O 2 was examined under the constant potential in the range of Fe 2+ dosage from 0 to 1.0 mM. The amount of generated OH radical initially increased and gradually decreased after the maximum was reached. The initial rate of OH radical generation increased for the Fe 2+ dosage <0.25 mM and at higher Fe 2+ dosages remained constant. At higher Fe 2+ dosages the precipitation of Fe might inhibit the enhancement of OH radical generation. The experiments for decolorization and total organic carbon (TOC) removal of azo-dye Orange II by the electro-Fenton process were conducted and the quick decolorization and slow TOC removal of Orange II were found. To quantify the linkages of OH radical generation with dynamic behaviors of electro-chemically generated H 2 O 2 and iron redox cycle and to investigate effects of OH radical generation on the decolorization and TOC removal of Orange II, novel reaction kinetic models were developed. The proposed models could satisfactory clarify the linkages of OH radical generation with electro-chemically generated H 2 O 2 and iron redox cycle and simulate the decolorization and TOC removal of Orange II by the electro-Fenton process.